SISTEM INFORMASI GEOGRAFIS LETAK PENYEBARAN TEMPAT PARIWISATA DI KABUPATEN MAJALENGKA DENGAN MENGGUNAKAN METODE DIJKSTRA - Ade Bastian; Abdul Kholik; Miftahuddin Al-Aziz (PROCEEDING STIMA)
The tourism sector is one of the productive potential until today continuously developed. Potential and tourist wealth in Majalengka that many tourist attractions but the lack of promotion of the government prompted the authors to develop a Geographic Information System. Majalengka has a wide range of tourist attractions that have the charm of each, both natural and cultural charm can certainly be used as capital to further develop this area as a tourist destination. Therefore, the provision of accurate data about the condition of the tourist attractions in Majalengka indispensable. In terms of tourists or visitors, travel information is needed to plan a trip from the residence or place of origin to the place of destination. In addition to in order to get a clear picture of the state of the places to be visited, tourists also can set up costs and the appropriate equipment for the trip in order to avoid things that are not desirable. Information concerning, among other tourist attractions, accommodations, and distance to the sights. Besides aiming to market the tourism products, also aims to provide complete information for potential tourists to be able to visit the tourist place. The development of tourism in Majalengka would bring many benefits to society, which is economically, socially and culturally. The elements of a well-managed tourism can provide benefits to the area.Keywords : Tourism, Geographic Information System, Majalengka District.